Predictive factors for persistent postoperative hydrocephalus in children undergoing surgical resection of periventricular tumors - Chen, Zitao; Zhou, Ming; Wen, Huantao; Wang, Qiang; Guan, Jianwei; Zhang, Yuan; Zhang, Wangming (Frontiers in Neurology, 2023)
Objective: This study is aimed at identifying the factors predicting persistent hydrocephalus after periventricular tumor resection in children and assessing the need and efficacy of perioperative cerebrospinal fluid (CSF) intervention. Methods: We performed a retrospective analysis of pediatric patients who underwent resection surgery of the periventricular tumor between March 2012 to July 2021 at the Department of Neurosurgery in Zhujiang Hospital of South Medical University. Demographic, radiographic, perioperative, and dispositional data were analyzed using univariate and multivariate models. Results: A total of 117 patients were enrolled in our study. Incidence of postoperative persistent hydrocephalus varied with tumor pathology (p= 0.041), tumor location (p = 0.046), surgical approach (p = 0.013), the extension of resection (p = 0.043), tumor volume (p = 0.041), preoperative Evan’s index (p = 0.002) and preoperative CSF diversion (p=0.024). On logistic regression, posterior median approach (OR=5.315), partial resection (OR=20.984), volume > 90cm3 (OR=5.768), and no preoperative CSF diversion (OR=3.661) were independent predictors of postoperative persistent hydrocephalus. Preoperative Evan’s index is significantly correlated with tumor volume (p=0.019). Meanwhile, the need for preoperative CSF drainage in patients in this cohort was significantly correlated with tumor location (p=0.019). Conclusion: Tumor pathology, location, surgical approach, the extension of resection, tumor volume, preoperative Evan’s index, and preoperative CSF diversion were considered to be predictive factors for postoperative persistent hydrocephalus. Notably, posterior median approach, partial resection, and tumor volume > 90cm3, without preoperative CSF diversion were identified as independent risk factors for persistent postoperative hydrocephalus. Preoperative identification of children at risk for developing persistent postoperative hydrocephalus would avoid delays in planning the cerebrospinal fluid diversion. Active and effective preoperative hydrocephalus intervention in children with periventricular tumors is beneficial to reduce the incidence of persistent hydrocephalus and ventriculoperitoneal shunt surgery after resection.